Forming the Terminology of Russian Phonetics: Diftong ‘Diphthong’ - Andrey V. Ivanov (RUDN Journal of Language Studies, Semiotics and Semantics)
The aim of the article is to describe the history of the occurrence of the term diftong ‘diphthong’ and its synonymous nominations in the terminological system of Russian linguistics, to analyze linguists’ points of view on diphthong as a sound phenomenon in the period from the 14th century to the 18th century. Based on the analysis of scientific (grammars, grammatical works) and lexicographical (lexicons, dictionaries) sources, appeared in Russia in the 14th-18th centuries, the author traces the evolution of the phonetic status of diphthong, which in line with the traditions, laid down by the creators of Slavonic and Russian grammars, for a long time was treated in accordance with the Greek tradition, being transmitted in writing by one or two letters. Taking this approach into account, quasidiphthongal combinations, digraphs and even affricates, which were not peculiar to the Russian language, were treated as diphthongs. By the end of the 18th century, the scientific-linguistic paradigm in the sphere of sound system study underwent certain changes; many phonetic phenomena were reinterpreted, and simultaneously the approach to the evaluation of the linguistic status of diphthongs changed, though diphthongal sound-combinations were still considered to be a part of the Russian vocalizm. Diphthong is unambiguously described as a complex sound that consists of two vowel letters and forms one syllable. Throughout its existence this notion, along with the Greek etymon borrowed into Russian and gradually assimilated, received several synonymous nominations, which were structural-semantic loan translations of the borrowed word: dvoglasnaya (14th c.), dvoeslozhnaya (14th c.), dvoeglasnaya (1578), dvoslozhnaya (17th c.), dvuglasnaya (1739), polglasie (1769), slozhnaya (1779), slozhennaya (1788). Almost all of these names reflected the bivocalic nature of the diphthong as a phonetic phenomenon. The research employs methods of historical-linguistic, definitional and semantic analysis.